QUAL O PAPEL DO SISTEMA IMUNE NAS MORTES POR MALÁRIA? - Basilio, Gabriel Ferraz Campos; Santana, Lucília Fraissat; Moreira, Matheus (Revista de Patologia do Tocantins, 2019)
biológico complexo que pode causar diferentes reações imunes no organismo. Essa resposta imune leva a manifestações leves ou graves da doença. O objetivo deste trabalho é abordar o papel do sistema imune na fisiopatologia da malária e suas complicações. Visando assim, definir a melhor abordagem a ser seguida pelas novos trabalhos em terapêutica da malária. Palavras-chave: malária; sistema imune; fisiopatologia; complicações. ABSTRACT Malaria is one of the leading global health issues; it causes more than a million deaths each year. In Brazil, malaria cases are mainly concentrated in the north region of the country. The disease is caused by a complex biological cycle parasite which can cause different immune reactions in the body. This immune response leads to mild or severe manifestations of the disease. The objective of this work is to address the role of the immune system in the pathophysiology of malaria and its complications. In this way, we can define the best approach to new research in malaria therapy. Keywords: malaria; immune system; physiopathology; complications.